201k views
5 votes
Let f(x)=5x-4 and g(x)=x^2-1. Find (g*f)(-1)

Let f(x)=5x-4 and g(x)=x^2-1. Find (g*f)(-1)-example-1
User Wloleo
by
6.1k points

1 Answer

3 votes

Answer:

D. 80

Explanation:

Given:

f(x) = 5x - 4,

g(x) = x² - 1

Required:

(g o f)(-1)

SOLUTION:

(g o f)(-1) = g(f(-1))

Plug in -1 for x into the function, f(x) = 5x - 4:

g(f(-1)) = g(5(-1) - 4)

= g(-5 - 4)

= g(-9)

Plug in -9 for x in the function, g(x) = x² - 1

g(-9) = (-9)² - 1

= 81 - 1

= 80.

Therefore, (g o f)(-1) = g(f(-1)) = 80

D. 80 is the correct answer.

User Wjatek
by
5.1k points